Strategic Directions for Organization Sustainability (Journal of Universal Excellence, 2026)
Research Question (RQ): Do we need sustainable governance and management of the organization to introduce a strategic concept of organizational sustainability?Purpose: The concept of sustainability must be woven into every pore of individuals, companies, and other organizations as well as economy and the society, and thus also nature and the natural environment, which provide us with a necessary condition for our survival. In the article we present the importance of integrating sustainability into strategic directions of organizations.Method: We use qualitative research. The key findings of the research are based on the use of a case study. The article is also the result of using the Dialectical Systems Theory and presents the results of a sufficiently holistic approach.Results: We present a good practice example of how to integrate the concept of sustainability into the strategy of a large organization. The key result comes from the finding of the importance of the strategic orientation of the organization's sustainability for individuals, organizations, economies, society, and nature.Organization: Sustainable governance, management, development, and operations must be targeted, and with them the organization gains a competitive advantage. Multi-stakeholder partnerships can form the basis for the strategic concept of sustainable development of an organization.Society: The presented method of long-term sustainable development and business-oriented operation of organizations can enable humanity to eliminate the consequences of past and current irresponsible behaviour, and at the same time it also represents an important originality and value of this article.Originality: Theoretical starting points on sustainable development, sustainable development goals, achieving sustainable development in the organization (by focusing on governance, management, and development), multi-stakeholder partnerships (which can be the basis for the strategic concept of organizational sustainability) were used as a starting point for the research of academic communities as part of multi-stakeholder partnerships to achieve the goals of sustainable development. We have studied the sustainable governance and management of universities and, from the studied aspects, researched the case of the sustainable University of Maribor, which we propose as a suitable partner for establishing a strategic concept of sustainability. We have not found such research in the literature known to us.Limitations/Future Research: We limit ourselves to the presented theoretical aspects of the theory of sustainable development and its goals, among them on multi-stakeholder partnerships, models of integral management when studying the achievement of sustainable development goals in the organization, a case study of academic communities and, in this context, the University of Maribor. In the future, we propose to carry out a comparative analysis of the presented example of the university with some other university and to investigate examples of good practice of academic communities in the role of a multi-stakeholder partner in the context of achieving the goals of sustainable development.
Keywords: responsible governance; strategic management; strategy; sustainability; sustainable development; social responsibility